Preparation of a type of water evaporation inhibiting monolayer based on epoxy resin. Issue 6 (10th August 2015) - Wu, Yan; Yang, Fangming; Zhang, Xuan
Abstract: In this paper, a type of water evaporation inhibiting monolayer was synthesized through the reaction of hydrogenated bisphenol A epoxy resin with hexadecanol and butanol. These are termed epoxy resin‐based monolayers (ER series). By means of π–t isotherms, γ –C isotherms, evaporation resistance and time, the spreading properties of ER series at gas/liquid interface and the capability of restraining water evaporation were studied systematically. The compactability and morphology of monolayer were characterized by Maxwell displacement current and atomic force microscopy. The results revealed that ER series could spread spontaneously at air/water interface to form a compact, condensed and stable monolayer. Comparing with hexadecanol, the monolayer presented a better performance of restraining water evaporation. Copyright © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.